A People’s Criminologist in An Age of Trumpian Populism: On the Praxis of Newsmaking and Monetizing - Barak, Gregg (Advances in Social Sciences Research Journal, 2022)
This self-ethnography is about a radical or people’s criminologist in an age of Trumpian populism. It offers a case study on the theory and practice of newsmaking criminology and of monetization of the Trump book industry. After establishing what newsmaking criminology is as the originator of the concept and providing an overview of 35 years of newsmaking, I pivot to an examination of three elements—commentaries, publicity, and digital content—that are associated with “socially mediated newsmaking” and the monetizing of Trump, criminology, and criminologists. This is followed by a discussion and evaluation of the merits of newsmaking criminology in general and of this newsmaking excursion into social media. Finally, I call for more criminologists to become newsmakers to take on the “crimes of omission” by the 4th Estate.